PERSPEKTIF UU NO. 24/2009 TERHADAP LEGALITAS KONTRAK BISNIS INTERNASIONAL YANG BERMODEL MONOLINGUAL ASING - Encep Mindar R; Elan Jaelani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The development of contracts in international business contract currently has implications for existing legal arrangements, especially arrangements within the scope of business law. New aspects in the scope of international business really need attention, onee of which is uthe uuse of language in ann international business contract. The use of language in international business contracts is a separate concern considering that this aspect is one of the mostt importantt parts that will have a direct impact on the implementation of a business contract. This legal research uses a normative juridical method. The resultsf of the researchy in this papero show that afterx the Law No.24/2009 existed, arrangements regarding the use of Indonesian in international business contracts have been regulated as in article 31. However, this article does not contain strict sanctions against violators, giving rise to legal uncertainty